National Context, Parental Socialization, and the Varying Relationship Between Religious Belief and Practice - Voas, David (Journal for the scientific study of religion, 2021)
Parents are crucial agents of religious socialization, but the broader social environment is also influential. A key question is whether parents are more or less influential when their religious beliefs and practices are not shared by people around them. Current thinking on the issue has largely been shaped by Kelley and De Graaf, who argued that parental religious socialization matters most in secular countries. We maintain that that conclusion is mistaken: levels of parental and national religiosity are both important, but their effects are largely independent of each other. Kelley and De Graaf's findings rely on the assumption that religious belief and practice are different expressions of the same underlying phenomenon (religiosity) and vary in the same way across time and space. These measures are not equivalent, however. In relatively religious societies, belief in God is widespread even among those who do not attend services, whereas in societies where religious involvement is low, nonchurchgoers tend to be nonbelievers.